2020
DOI: 10.1016/j.compbiomed.2020.103755
|View full text |Cite
|
Sign up to set email alerts
|

SegSRGAN: Super-resolution and segmentation using generative adversarial networks — Application to neonatal brain MRI

Abstract: Background and objective: One of the main issues in the analysis of clinical neonatal brain MRI is the low anisotropic resolution of the data. In most MRI analysis pipelines, data are first re-sampled using interpolation or single image super-resolution techniques and then segmented using (semi-)automated approaches. In other words, image reconstruction and segmentation are then performed separately. In this article, we propose a methodology and a software solution for carrying out simultaneously high-resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Since its introduction, there has been a surge of interest in the application of GAN frameworks related to the brain. Some of the applications include image generation with improved properties such as achieving super resolution or better quality [6][7][8][9][10][11], data augmentation [12][13][14], segmentation [9,[13][14][15][16], image reconstruction [17][18][19][20], image-to-image translation [21][22][23][24], and motion correction [25,26]. While these important studies have demonstrated the exciting prospect of using GAN architectures, there is a limited amount of work that has focused on utilizing the generated images for subsequent tasks such as disease classification [27].…”
Section: Introductionmentioning
confidence: 99%
“…Since its introduction, there has been a surge of interest in the application of GAN frameworks related to the brain. Some of the applications include image generation with improved properties such as achieving super resolution or better quality [6][7][8][9][10][11], data augmentation [12][13][14], segmentation [9,[13][14][15][16], image reconstruction [17][18][19][20], image-to-image translation [21][22][23][24], and motion correction [25,26]. While these important studies have demonstrated the exciting prospect of using GAN architectures, there is a limited amount of work that has focused on utilizing the generated images for subsequent tasks such as disease classification [27].…”
Section: Introductionmentioning
confidence: 99%
“…Their models outperformed previous models with an overall 0.66%. A Super resolution and segmentation using generative adversarial networks is a framework introduced by [30] to neonatal brain M RI. It consists training a generating network that estimates for a given input image to its corresponding HR, and a discriminator network D is designed to distinguish real HR and segmentation images.…”
Section: B Generative Adversarial Networkmentioning
confidence: 99%
“…Their models outperformed previous models with an overall 0.66%. A Super resolution and segmentation using generative adversarial networks is a framework introduced by [31] to neonatal brain M RI. It consists training a generating network that estimates for a given input image to its corresponding HR, and a discriminator network D is designed to distinguish real HR and segmentation images.…”
Section: B Generative Adversarial Networkmentioning
confidence: 99%